Association between physical activity and executive function of Chinese adolescents aged 13–18 - Liu, Yuan; Yin, Xiaojian; Sun, Yi; Zhang, Feng; Bi, Cunjian; Guo, Yaru; Sun, Pengwei; Jun, Hong; Hu, Yanyan; Liu, He (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to investigate the relationship between physical activity (PA) and executive function (EF) among adolescents in China.MethodsUsing a stratified cluster random sampling, we recruited 4,991 adolescents from 11 Chinese cities, including Urumqi, Lhasa, and Naqu etc. Participants completed execution function test and PA questionnaire survey. Data were analyzed using one-way ANOVA, Pearson correlation analysis, and 30-minute isotemporal substitution models (ISM) to assess the association between PA and EF.ResultsDaily moderate-to-vigorous physical activity (MVPA) time in both boys and girls was negatively correlated with inhibitory control RTs (r = −0.279, −0.173, P < 0.01), 2back-RTs (r = −0.367, −0.268, P < 0.01), and cognitive flexibility RTs (r = −0.283, −0.305, P < 0.01). Replacing 30 min of sedentary behaviour (SB) with MVPA was significantly shorter RTs in inhibitory control (P < 0.05), 2back tasks (P < 0.01), and cognitive flexibility (P < 0.01). Similarly, substituting 30-min of light physical activity (LPA) with MVPA led to reduced RTs in all three EF domains (P < 0.05 for inhibitory control; P < 0.01 for others). After adjusting for covariates, a U-shaped dose-response relationship emerged between MVPA duration and EF performance. Adolescents with 59.02–60.88 min/day of MVPA (the relatively high-level group) demonstrated the lowest RTs in inhibitory control, working memory, and cognitive flexibility (P < 0.05).ConclusionsAfter controlling for confounders, MVPA exhibited an inverted U-shaped relationship with inhibitory control, working memory, and cognitive flexibility. Optimal EF improvement was observed at 59.02–60.88 min/day of MVPA, suggesting this range may be most beneficial for adolescents’ executive function.